A Guerra da Notícia – A política do silêncio no Jornal Nacional e no discurso de Jair Bolsonaro relatado pelo telenoticiário na pandemia de Covid-19 - Figueira Sobrinho, Nelson (2024)
This work is based on the premise that the Covid-19 pandemic caused a series of ruptures that forced society to modify its customs, transformed ways of being and saying and made our words become enchanted with “pandemic meanings” (ORLANDI, 2020a). These new ways of saying and reaching traditional media outlets as well. One of the media outlets that suffered this tension was Rede Globo de Televisão, especially Jornal Nacional, the most watched television news program in the country, which apparently fought a war of words with the then president, Jair Bolsonaro, with the theme being the fight against the pandemic and to its effects. Using Franco-Brazilian Discourse Analysis as a theoretical-methodological procedure, this research aims to study this relationship between JN and the then president based on Eni Orlandi's (1987, 2007a) theories on the category of silence, specifically on the politics of silence, which is divided into constitutive silence and local silence, a censorship. In this sense, we analyze how the policy of silence is processed in JN's speeches in materials directly and indirectly related to the Covid-19 pandemic, with emphasis on local silence, which acts to prohibit the subject's inscription in certain discursive formations. Likewise, the objective is to analyze whether, even though they were cut by the news broadcast and used during the reported speech, the ex-president's words were also intended to be silenced locally. We assume that the policy of silence works in JN's discourse as a way of promoting eliminations and censorship and that by discursively placing its occupied position (or not) with the position of former president Jair Bolsonaro in facing the crisis, Jornal Nacional acted with a view to 2022 elections. We understand that under the pretext of providing a service to the population during a health, social and humanitarian crisis, the news sought to reposition itself in front of the Brazilian public and regain a role it has played since its creation in the sense of ideologically influencing Brazilian society. In addition to Orlandi's theorizations about silence (2007a, 1987), the research focuses on Pêcheux (1999, 2014a, 2014b, 2014c, 2015), with a view to discussing basic concepts such as imaginary formations, discursive formations, ideological formations, memory, interdiscourse and others. Furthermore, it is also based on Authier-Revuz (1990, 1998, 2004, 2015) to discuss reported speech and the representation of other speech. In the end, we infer that there are more convergences than divergences between JN and Bolsonaro's speeches, even if cut and reported by the news. Both, enrolled in a Neoliberal FD, disagree only on methods, but have similar discourses regarding the maintenance of neoliberal processes and instruments, such as necropower and libertarian paternalism.